Of standards and technology: ISDA and technological change in the OTC derivatives market. Issue 1 (3rd April 2021) - Schammo, Pierre
ABSTRACT: For enthusiasts, distributed ledger technology (DLT) and smart contract technology (SCT) promise a future of frictionless interactions and decentralisation. In practice, however, it is widely acknowledged that this vision faces significant challenges. These include legal challenges, technological challenges, but also implementation challenges. The latter arise because delivering the DLT/SCT vision does not take place in a vacuum, but in a setting populated by existing market actors that operate on the basis of pre-existing technologies and absent an industry-wide layer of standards to support technological change and the vision of frictionless interactions. This article seeks to contribute to the literature interested in implementation challenges. Its aim is two-fold: to examine implementation challenges and to take stock of current market efforts to overcome them. In particular, this article focusses on the efforts of the International Swaps and Derivatives Association (ISDA) and its initiatives to 'standardise to digitise'. It will show that these initiatives can usefully be examined as an attempt to help the industry coordinate on a common foundational standards layer. However, this article also finds that the success of ISDA's efforts is by no means certain. Nor are its efforts without raising some concerns.